If you give a moose a muffin - Numeroff, Laura Joffe; Bond, Felicia ([New York] : Laura Geringer Book, 1991)
Shows the chaos that can ensue if one gives a moose a muffin and starts him on a cycle of urgent requests.
Sequel to: If you give a mouse a cookie.
"A Laura Geringer Book.".
School Library Journal starred, June 2000.
School Library Journal, June 2000.
Book Links (A.L.A.), July 2005.
School Library Journal starred.
Keywords: Moose -- Fiction; Moose -- Fiction; Moose -- Fiction